A fast and accurate mean radiant temperature model for courtyards: Evidence from the Keyuan Garden in central Guangdong, China. (1st February 2023) - Wu, Renzhi; Fang, Xiaoshan; Liu, Shuang; Middel, Ariane
Abstract: Most models that simulate mean radiant temperature ( T mrt ) for complex geometries are computationally expensive. We developed a fast and accurate T mrt model for courtyards (CMRT) based on a parallelized quasi-physical algorithm. Here, we present the CMRT implementation, validate the model for Keyuan Garden in Central Guangdong, and compare model results and performance to ENVI-met and Ladybug Tools. The new model simulated T mrt for various locations in the test bed courtyard with a root mean square error ( RMSE ) of 1.82 °C, outperforming Ladybug (5.00 °C) and ENVI-met (8.27 °C) and meeting the accuracy requirement for heat and cold stress. The CMRT model simulates T mrt two orders of magnitude faster than ENVI-met and Ladybug Tools. Model performance increased with resolution of the domain and number of view facets. A sensitivity analysis shows that the solar beam fraction is the largest contributor to T mrt after air temperature. Cloud cover has a non-linear effect on T mrt, and every 1 °C increase in surrounding surface temperatures raises T mrt by 0.28 °C. With faster simulations and reliable results, the CMRT model will facilitate future climate-resilient courtyard design. Highlights: A parallelized quasi-physical algorithm simulates courtyard mean radiant temperature. Model validation using in-situ observations shows model efficiency and accuracy. Surface/canopy temperature modeling improvements enhance longwave radiation results. Optimized model facilitates assessment of climate-adaptive courtyard design.